The EXTrauterine Environment for Neonatal Development: Present and Future. (May 2022) - Larson, Abby C.; De Bie, Felix R.; Chang, Jonathan; Davey, Marcus G.; Flake, Alan W.
Despite advances in clinical care and modest improvement in mortality rates for extreme prematurity, morbidity remains a significant challenge. The ideal environment to support prematurity would be fluidic and rely on natural fetal circulation to mimic the natural fetal amniotic environment, yet such an environment has been unsuccessful in long-term support until recently. Our group has succeeded in developing such a support system to foster fetal growth in the premature lamb model that shows promise for clinical translation. Here, we describe the EXTrauterine Environment for Neonatal Development (EXTEND) from its conception onwards, review published literature on fetal development and support of the premature lamb model in EXTEND, and discuss future applications.